HUBUNGAN PERAN KELUARGA TERHADAP KEAKTIFAN MENGIKUTI SENAM LANSIA - Anggraeni, Ayu (Politeknik Kesehatan Kemenkes Bengkulu, 2015)
The role of family at affective, socialization, health care affects the elderly inincreasing active in efforts improved health in physical, mental, social and efforts to increase lifeexpectancy that is free from distractions.Risert purpose to determine the role of the FamilyRelationships Following Gymnastics Against Elderly Motivation In Work Area Health CenterBuild Jaya in 2014.This study used a cross sectional design, engineering to get samples usingcluster random sampling the samples of 54 elderly health centers in the Work Area Jaya Build2014. Processed data using univariate and bivariate using Chi Square test.Most of respondents(75.9%) female, the majority of respondents (53.7%) had a poor family role and most of therespondents (61.1%) active follow gymnastics elderly. There is a relationship between the role ofthe family with the liveliness of the elderly with a p=0.001 CI: 95%. The role of family it will bevery influential to give a support on the increased activity of the elderly so that physicalfunctioning, mental, social get a good care anyway.